PEMBINAAN MASYARAKAT DESA PLALANGAN PONOROGO DALAM PENGOLAHAN LIMBAH PETERNAKAN UNTUK MEWUJUDKAN LINGKUNGAN BERSIH - Kuntang Winangun; Munaji Munaji; Bambang Wahrudin; Nanang Suffiadi Akhmad (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2026)
This community service program aims to increase the capacity of the Plalangan Village community, Jenangan District, Ponorogo Regency, to process livestock waste into useful products, specifically organic fertilizer. The main problems faced by partners are the low understanding and skills of waste management, as well as poor environmental sanitation due to the accumulation of livestock manure. The implementation method is carried out through a participatory approach in the form of socialization, technical training, and ongoing mentoring. The results show a significant increase in community knowledge and skills, as evidenced by the implementation of waste processing into solid and liquid organic fertilizer by the PemudaMu Farm partner group. This program also encourages environmental awareness and new economic opportunities based on the utilization of livestock waste. Thus, this community service activity contributes to improving community welfare while supporting sustainable development in the livestock sector.